Lost in Geography: Croatia’s Identity Crisis - Botić, Jurica (European Journal of Geography, 2026)
Historically situated at the geographic crossroads of former Austro-Hungarian and Venetian territories along the westernmost Ottoman border and having experienced two Yugoslav states in the 20th century, contemporary Croatia is shaped by diverse spatial identity influences. Drawing on the theoretical frameworks of border identities and regional institutionalisation, this paper explores the identity profiling of modern Croatia within the context of European regionalisation. The research employs a methodological triangulation of diverse discursive sources—including an analysis of geography textbooks, official state documents, and tourism branding—contrasted with media reports and an extensive public survey conducted among a sample of 456 respondents. Specifically, Croatia’s official discourse prioritises its affiliation with the Central European and Mediterranean spheres while strategically marginalising the Balkan context often using Southeast Europe as a more neutral geopolitical substitute. Conversely, the findings reveal a layered identity construct among the public, where Mediterranean, Central European, and Balkan geo-cultural spheres overlap. The results suggest that contemporary Croatia functions as a geographic transition zone where multiple regional frameworks interweave into a multidimensional sense of place, without the territory being fixed within a single regional entity. Highlights: A gap exists between official discourse and public perception of Croatia’s regional affiliation. Croatia functions as a geographic transition zone with overlapping regional spheres. The strategic significance of Mediterranean rebranding for Croatia.